Collaborative economy-based business incubator model to increase the intention of Islamic entrepreneurship - Aeni, Reni Qurroti; Kardeli, Awang Dodi; Rahayu, Meirani (Fakultas Ekonomi dan Bisnis Islam, 2023)
The development of entrepreneurship education is intricately linked to individual interactions within their environment. This research aims to develop a collaborative economy-based business incubator model for fostering Islamic entrepreneurship intention. Employing a research and development methodology, the study involved 32 Pesantren youths at Taslim Pangalengan, focusing on a coffee-growing business unit. Data collection incorporated interviews, surveys, and limited group discussions. The analysis adopted a quantitative approach with various tests and qualitative descriptive analytics. Results revealed that changes in Islamic entrepreneurship behavior, seen as a social interaction process, are positively influenced by a collaborative economic system. Collaborative experiences contribute to strengthening the transformative aspects of thinking, behavior, and action, particularly in innovating and undertaking business risks. The business incubator emerges as a facilitator in shaping Islamic entrepreneurship intention. The study underscores the importance of enhancing comprehension of collaborative economics and business incubators to cultivate Islamic entrepreneurial intentions. It advocates for a broader perspective on entrepreneurial intentions grounded in Islamic principles within a collaboration-based business incubator model.